Implementing lean in Malaysian universities: Lean awareness level in an engineering faculty of a local university - Khairi, M. Azim; Abd Rahman, Mohamed (Institute of Physics Publishing, 2018)
Many academic articles were published in Malaysia promoting the goodness of lean in manufacturing and industrial sectors but less attention was apparently given to the possibility of obtaining the same universal benefits when applying lean in non-manufacturing sectors especially higher education. This study aims to determine the level of lean awareness among a local university’s community taking its Faculty of Engineering (FoE) as the case study. It also seeks to identify typical FoE’s staff perception on lean regarding its benefits and the obstacles in implementing it. A web-based survey using questionnaires was carried out for 215 respondents consisting of academic and administrative staff of the faculty. Statistical Package for the Social Science (SPSS) was used to analyze the survey data collected. A total of 13.95% of respondents returned the forms. Slightly more than half of those responded (56.7%) have encountered some of the lean terms with mean 1.43 and standard deviation 0.504. However, the large amount of standard deviation somewhat indicates that the real level of lean awareness of FoE as a group was low. In terms of lean benefits, reduction of waste was favored (93.3%) by the respondents with mean 0.93 and standard deviation 0.254. For obstacles in implementing lean, lack of knowledge was selected by most respondents (86.7%) to be the major factor with mean 0.87 and standard deviation 0.346. Through the analysis done, the study may conclude that level of lean awareness among the university‘s community was low thus may hinder implementation of lean concept.